Non-verbal Communication Training as the Soft Skill Development for PAUD Educator at Pakal Surabaya - Dewi Khrisna Sawitri; Wiwik Handayani; Ika Korika Swasti (Nusantara Science and Technology Proceedings, 2022)
As an educator, soft skill plays an important factor in teaching performance. Communication skill is beneficial as educators are interacting with their students. PAUD educators need to develop their communication skills since this skill is very beneficial for them while dealing with their early childhood students. In this community service, soft skill training for PAUD educators in Pakal district is given to focus on nonverbal communication development as they are about to conduct a face-to-face meeting with their students. There were 25 participants of Bunda PAUD (the term for PAUD educators) from 25 different PPTs (Pos PAUD Terpadu) who joined the training. The training had two sessions in which participants not only learn types of nonverbal communication but they also practice implementing nonverbal communication in Roleplays. They learn to implement haptics to calm students while they are having problems. They also practice maintaining distance (proxemics) by entering into students’ distance and try to perform eye behavior by showing eye contact while speaking with their early childhood students. This community service results in the development of Bunda PAUD’s nonverbal communication that exists during the monitoring and evaluation session of the Community service Team in some PPTs.